Membangun Spiritualitas Digital bagi Generasi Z - Adhika Tri Subowo (Sekolah Tinggi Teologi Intheos Surakarta, 2021)
Abstract. Generation Z is a generation that is close to digital technology, so the use of digital space as a teaching tool is important for churches to do. The dichotomy of sacred and profane often colors the perception of the church in seeing the digital space, so that digital space has not been fully utilized. This research was intended propose the suitable digital spirituality for generation Z. This study was conducted by literature study. Through this study it could be concluded that cyberspace has become part of the generation Z spirituality, although the interactions and conversations in it are not always spiritually charged, therefore, the church needs to be involved in it to be able to provide guidance to generation Z.Abstrak. Generasi Z adalah generasi yang dekat dengan teknologi digital, sehingga penggunaan ruang digital sebagai sarana pengajaran menjadi penting untuk dilakukan oleh gereja. Dikotomi sakral dan profan seringkali mewarnai persepsi gereja dalam memandang ruang digital, sehingga ruang digital belum dimanfaatkan dengan maksimal. Penelitian ini dimaksudkan untuk mengusulkan spiritualitas digital yang tepat bagi generasi Z. Metode yang digunakan dalam kajian ini adalah studi literatur. Melalui kajian tersebut dapat disimpulkan bahwa cyberspace telah menjadi bagian dari spiritualitas generasi Z, meskipun interaksi dan percakapan di dalamnya tidak selalu bermuatan rohani, sehingga gereja perlu ikut terlibat di dalamnya untuk dapat memberikan bimbingan kepada generasi Z.